Microsatellite primers for the rare sedge Lepidosperma bungalbin (Cyperaceae) - Nevill, Paul; Wardell-Johnson, G. (2016)
Premise of the study: Microsatellite markers were developed for the rare sedge Lepidosperma bungalbin (Cyperaceae) to assess genetic variation and its spatial structuring. Methods and Results: We conducted shotgun sequencing on an Illumina MiSeq and produced 6,215,872 sequence reads. The QDD pipeline was used to design 60 primer pairs that were screened using PCR. We developed 17 loci, of which 12 loci were identified that were polymorphic, amplified reliably, and could be consistently scored. We then screened these loci for variation in individuals from three populations. The number of alleles observed for these 12 loci across the three populations ranged from nine to 19 and expected heterozygosity ranged from 0.41 to 0.89. Conclusions: These markers will enable the quantification of the potential impact of mining on genetic variation within L. bungalbin and establish a baseline for future management of genetic variation of the rare sedge.